Market Study and User Behavior Analysis on Battery Charging Adoption for 2W-EV in Indonesia - Mubarok, Moh. Wahyu Syafiul; Darmawan, Yasmin Farhaini; Kartini, Evvy; Drew, Alan J (Journal of Batteries for Renewable Energy and Electric Vehicles, 2024)
The rapid expansion of the electric vehicle (EV) market has driven a global shift towards sustainable transportation solutions, with two-wheel electric vehicles (2W-EVs) playing a pivotal role in emerging economies like Indonesia. This study investigates the factors influencing the adoption of 2W-EVs in Indonesia, focusing on user behavior, charging preferences, and market dynamics. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews to gain a comprehensive understanding of consumer attitudes and preferences. The findings reveal that home charging is the preferred method for the majority of users, primarily due to its convenience and cost-effectiveness. However, significant barriers such as range anxiety, insufficient public charging infrastructure, and high upfront costs are impeding widespread adoption. The study also explores the complex interplay of market dynamics, including the influence of government policies, infrastructure development, and economic conditions on the 2W-EV market in Indonesia. Based on the analysis, this paper offers recommendations to accelerate 2W-EV adoption, including the expansion of charging infrastructure, cost reduction strategies through subsidies and incentives, and increased consumer education. The research concludes that while 2W-EVs have the potential to significantly contribute to Indonesia's sustainable transportation goals, achieving widespread adoption will require coordinated efforts across multiple sectors.